Empathetic Leadership, Innovative Work Behavior and Health Protocol Culture as Determinants of Employee Performance in Government Organizations - Naritasari, Naritasari; Surwanti, Arni; Qamari, Ika Nurul (Journal of Governance and Public Policy, 2023)
Employee performance is an interesting topic of debate because it determines the success and growth of an organization. This study aimed to analyze the effect of empathic leadership, innovative work behavior, and health protocol culture on employee performance. Respondents in this study were employees of Panggungharjo Village. Samples were taken using a saturated sampling approach with 101 employees. This research proved that empathic leadership strongly influenced employee performance with an original sample coefficient value of 0.194, a t-statistic value of 2.174, and a p-value of 0.0030. This research also discovered that empathetic leadership and innovative work behavior majorly influenced employee performance with an original sample coefficient value of 0.411 with a t-statistic and a p-value of 4.747 and 0.000. Health protocol culture had the strongest effect on employee performance during the pandemic and had an original sample coefficient value of 0.371 with a t-statistic and p-value of 5.122 and 0,000.